Magnetically actuated microrobotic system for sequential treatment of biofilm - Shunyao Li; Yu Mei; Kai Xu; Huaixuan Sheng; Yu-An Chen; Mingda Teng; Bohan Xu; Bingqian Jiang; Chengxuan Yu; Huizhu Li; Shiyun Zhao; Yi Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Biofilm-associated infections present a critical therapeutic challenge due to antibiotic resistance and impaired tissue healing. Here, we present a microrobotic system (MZ-8) that integrates real-time human-steered navigation with autonomous, microenvironment-responsive therapy to actively eradicate biofilms and promote tissue regeneration. This microrobotic system features a spine-inspired structure for mechanical biofilm disruption, a pH-responsive ZIF-8 coating for immunomodulatory Zn 2+ release, and closed-loop actuation under second near-infrared fluorescence guidance. In a rat model of periprosthetic joint infection, MZ-8 achieved effective biofilm removal, induced a pro-regenerative immune response by polarizing macrophages toward the M2 phenotype, and significantly enhanced tissue regeneration. Transcriptomic analysis further revealed the activation of immunomodulatory pathways and upregulation of M2-associated genes, confirming the system’s sequential shift from eradication to repair. Moreover, validation in a rabbit model and human knee joint confirmed its operational feasibility under clinical imaging guidance and excellent biosafety. This work establishes that integrating physical eradication, biochemical immunomodulation, and interactive control within a single system is essential for advancing from infection clearance to functional tissue restoration. Thus, it provides a therapeutic paradigm for biofilm-associated diseases and lays a foundation for future intelligent, clinically adaptive anti-infective systems.